A indústria metalúrgica na região de Pirapora- MG/Brasil: a distribuição da poluição por material particulado, sua composição e impactos associados - Elizêne Veloso Ribeiro (2016)
Urban and industrial development have generated a continuous increase in atmospheric pollutant emissions, among them stands up the particulate material. The presence of these pollutants in the atmosphere as well as their deposition can be responsible for diverse types of negative impacts at local, regional and global level. The plume formed by the atmospheric emissions of the metals industry in Pirapora-MG has called attention to the potential problems associated with air pollution in the region. In this context, the objective of this work was to analyze the air pollution by particulate matter caused by Silicon and Iron-Silicon industries in Pirapora. The methodological procedures included characterization and study of the spatial distribution of particulate plume based on climate data analysis, geomorphology and satellite images. Also, it was conducted the monitoring of atmospheric particulate at sampling stations in the municipalities of Pirapora and Buritizeiro. The emitted particulate matter and atmospheric particles were analyzed for size grain distribution, mineralogy determination (DFX), chemical (XRF, ICP-OES, TOF-SIMS) and morphological analyses (TEM, SEM, EPMA). Finally, heavy metals concentrations in soil samples (ICP-OES) were measured. In relation to the plume circulation, NE winds (31%) predominated, which determine a higher frequency of the movement of the plume SW (39.9%). The general direction to west, in more than 80% of the analyzed satellite images, place the urban localities in the area of higher deposition of the particles. The particulate material originated from these industries is characterized by amorphous silicon (95.52%), with particles in sizes between 0.18 and 123 µm, of which 30% are related to the inhalable fraction (< 10 µm). The chemical composition includes magnetite (FeO4), carbon, and metals like Zn, Cu, Pb, Cr and Ni. The atmospheric particles of industrial origin showed a spherical morphology, with its composition consisted mainly of Si, Fe, Ba and Cr. In the soils Fe (49360 ppm) e Cr (60,1ppm) concentrations showed higher values in the areas closest to the industrial district indicating the influence of the particulate material in the soil chemical composition. The presence of Cr in soil and spherical particles, including the inhalable particles, alert to the possible chronic effects on the health of local population. It is expected that the information about air pollution presented in this work can contribute to the management of environmental quality in the study area enabling the establishment of control and supervision systems of particulate matter emissions that includes the participation of the population.